Microstructure, mechanical, and magnetic properties of powder metallurgy FeCoNiSi–Cu, FeCoNiSi–Mn, and FeCoNiSi-Ti equiatomic HEAs manufactured by spark plasma sintering - Shimaa Abolkassem; Ayman Elsayed; Shota Kariya; Junko Umeda; Katsuyoshi Kondoh (Journal of Materials Research and Technology)
FeCoNiSi–Cu, FeCoNiSi–Mn, and FeCoNiSi–Ti equiatomic high entropy alloys (HEAs) were designed and produced via powder technology using spark plasma sintering (SPS). Metallurgical analysis tools, including SEM, XRD, EBSD, were used to investigate the crystal structure and the distribution of the formed phases for the prepared HEAs. The formation of a ductile FCC phase for all the prepared HEAs was observed, while the brittle BCC phase was formed only for FeCoNiSi–Mn HEA. By comparing the results with thermodynamic parameters, it is found that there is a strong agreement for the results with the valence electron concentration rule. FeCoNiSi–Cu and FeCoNiSi–Mn HEAs show 100% relative density, whereas FeCoNiSi–Ti HEA shows only 95%. All the prepared HEAs with Cu, Mn, and Ti additions show high hardness values of 507, 710, and 495 Hv, respectively. Both FeCoNiSi–Cu and FeCoNiSi–Mn HEAs have high compressive strength and yielding strength of 1854 MPa,1390 MPa for FeCoNiSi–Cu HEA and 1565 MPa, 1482 MPa) for FeCoNiSi–Mn HEA, respectively. Although having finer grains, FeCoNiSi–Ti HEA shows the lowest compressive strength and yield strength values. This is due to the tendency of the alloy to form intermetallic compounds and the presence of pores that act as nuclei for crack initiation and propagation. In addition, due to the presence of non-ferromagnetic elements in equiatomic ratio with other ferromagnetic elements (FeCoNi), FeCoNiSi–Cu HEA shows only 59.4 emu/gm for magnetization saturation, but the magnetic properties for both FeCoNiSi–Mn and FeCoNiSi–Ti HEAs nearly disappeared.The electrical resistivity for all the prepared HEAs is very high.